Clinical Evidence Of Thyroidinum In Hypothyroidism : A Case Based Approach - Gupta, Reetu Rani; Munjal, Shalu (Journal of Neonatal Surgery, 2025)
Hypothyroidism is a common endocrine disorder characterized by inadequate production of thyroid hormones, leading to a spectrum of systemic manifestations such as fatigue, weight gain, cold intolerance, constipation, hair fall, and mood disturbances. Conventional treatment typically requires lifelong levothyroxine replacement therapy, which is associated with concerns of compliance, dependency, and side effects. Homoeopathy, with its holistic and individualized approach, offers an alternative therapeutic modality. This case study highlights the role of Thyroidinum, a well-recognized homoeopathic remedy derived from the dried thyroid gland of sheep, in the management of primary hypothyroidism. A 35-year-old female with classical symptoms of hypothyroidism was treated over 6 months, assessed using Zulewski’s clinical score and laboratory parameters (TSH levels). Marked improvement was observed in both subjective symptoms and objective biochemical values, with enhanced quality of life and reduced reliance on allopathic medication